Visual Reaction Time: How it Relates to Body Mass Index, Dominant and Non-dominant Hand in Healthy Young Females - Jha, Reena Kumari; Thapa, Samjhana; Kasti, Roshan; Singh, Sumi (Nepal Medical College Journal, 2021)
Reaction time is an indirect index of the processing speed of the central nervous system. It is affected by several factors including dominant and non-dominant hands and obesity. Obesity can be measured by body mass index. Thus, the aim of this study was to find out the relationship between body mass index, dominant and non-dominant hand with visual reaction time in healthy young females. A cross-sectional study was conducted in the Department of Physiology, among 89 females. The height and weight were recorded, and the body mass index was calculated. The subjects were divided into four groups, underweight, normal weight, overweight, and obese according to WHO criteria. Visual reaction time was measured using the ruler drop method in milliseconds. The data were analyzed by using the paired t-test and one-way ANOVA using the IBM Statistical Package for the Social Sciences version 22. Out of 89 participants, 26 (29.21%) were underweight, 47 (52.80%) had normal weight, 12 (13.48%) and four (4.49%) were overweight and obese with mean reaction time in the dominant hand and non-dominant hand were (176.75±16.68 vs. 186.58±16.21), (175.12±15.03 vs. 185.43±15.64), (188.74±16.07 vs. 190.70±17.88), and (200.7±9.77 vs. 210.50±9.50) respectively. All participants were right-handers. In right-handers, the right hand reacted faster than the left hand. Reaction time was prolonged in underweight, overweight,and obese; when compared with normal weight individuals. Our study showed that the reaction time of people appears to be influenced by body mass index, dominant, and non-dominant hand, which was an indirect measure of the sensory motor association.